Designing Multimedia Applications for Nutrition Education and Managing Stress - Kasmana, Kankan; Dewi, A. C.; Hermiyah, M.; Asifa, V.; Maulana, Hanhan (Universitas Pendidikan Indonesia (UPI), 2021)
This research is a project, which is a multimedia application design that aims to provide education about the importance of balanced nutrition and stress management during the COVID-19 pandemic. The design is divided into several menus in applications that contain multimedia elements in the form of text, images, sound, animation, and video. Data obtained through a qualitative approach were taken by taking and analysing existing data to resolve the situation from interviews with participants as a user and informants. The multimedia development method used is the Multimedia Development Life Cycle (MDLC), which consists of the concept, design, material collection, manufacture, testing, and distribution stages. The design results show that collaboration between communication considerations, design, and information system structuring is required in the process. This multimedia application's design can support the process of providing education, increase interest in better understanding the behaviour of balanced nutrition, and deal with stress during the Covid-19 pandemic for users.